Continuous improvement in national ART standards by the RTAC accreditation system in Australia and New Zealand. (21st October 2016) - Harrison, Keith; Peek, John; Chapman, Michael; Bowman, Mark
Abstract : Background: Assisted reproductive technology (ART) clinics in Australia and New Zealand are accredited and licensed against a Code of Practice audited by certifying bodies accredited by the Joint Accreditation System for Australia and New Zealand (JAS‐ANZ). The system is administered by the Reproductive Technology Accreditation Committee (RTAC) of the Fertility Society of Australia. Aims: To review the incidence of variances and findings identified by certifying bodies in Australian and New Zealand ART clinics within the currency of a single version of the Code of Practice. Methods: Retrospective analysis of certifying body findings against the RTAC Code of Practice incorporating 15 Critical Criteria audited annually and 16 Good Practice Criteria including a Quality Management System audited over a three year cycle. Results: The incidence of clinics with variances against the Critical Criteria fell from 77 to 14% over two years, as did the mean number of variances per clinic which fell from 1.54 to 0.14. Conclusions: Implementation of the RTAC accreditation system in Australia and New Zealand has contributed to steady improvement in standards and a reduction in risk in ART treatments.